The politics of walls: Barriers, flows, and the sublime - CALLAHAN, William A. (Institutional Knowledge at Singapore Management University, 2018)
As Donald Trump’s presidential campaign showed, walls are a hot topic. While ‘globalisation’, with its free flow of capital and goods, characterised world politics after the end of the Cold War, the twenty-first century has witnessed a reassertion of cultural, legal, and physical barriers. It is common to criticise such post-Cold War walls, especially the US-Mexico Barrier and Israel’s West Bank Barrier, as ineffective and immoral. This article problematises such critical discourse by using unlikely juxtapositions (the Great Wall of China) and new conceptual frameworks (gaps, critical aesthetics) to explore: (1) how walls can be a rational security policy; (2) how they are not simply barriers, but can be complex sites of flows; and (3) how walls are not simply texts waiting to be decoded: they are also sites of non-narrative affective experience that can even excite the sublime. This critical juxtaposition of walls first explores what they can tell us about the politics of borders, identity, and foreign policy, and then considers how walls, as concrete visual artefacts, can be examples not simply of ideology, but also of affect. The article aims to understand walls in a different register as active embodiments of political debate – and of political resistance.